Assessing the quality of life in children with autism spectrum disorder: a cross-sectional study of contributing factors - Tedla, Jaya Shanker; Asiri, Faisal; Reddy, Ravi Shankar; Sangadala, Devika Rani; Gular, Kumar; Kakaraparthi, Venkata Nagaraj (Frontiers in Psychiatry, 2024)
ObjectiveThe study aimed to assess the quality of life (QoL) in children with autism spectrum disorder (ASD) compared to typically developing peers, identify key influencing factors such as socio-demographic and comorbid conditions, and examine the impact of symptom severity on QoL outcomes.MethodsIn this cross-sectional study conducted in Saudi Arabia, 75 children with ASD were compared to 75 typically developing children matched for age and gender. QoL was evaluated using the Pediatric Quality of Life Inventory (PedsQL), while the severity of autism symptoms was assessed using the Autism Diagnostic Observation Schedule (ADOS). Additional variables, including socio-demographic factors, comorbid conditions, and family environment, were collected through structured interviews and clinical assessments. Statistical analyses, including independent samples t-tests, multiple linear regression, and ANOVA, were employed to compare QoL scores, identify predictors, and assess the impact of symptom severity on QoL outcomes.ResultsThe mean overall QoL score for children with ASD was 57.86 (SD = 13.25) compared to 81.67 (SD = 10.89) for typically developing children (t = -10.56, p < 0.001, Cohen’s d = 1.90). Socioeconomic status (β = -0.25, t = -5.00, p < 0.001), comorbid ADHD (β = -0.35, t = -5.83, p < 0.001), and parental mental health issues (β = -0.45, t = -9.00, p < 0.001) were significant predictors of lower QoL. ANOVA results showed that children with severe autism symptoms had the lowest QoL scores (mean = 40.12, SD = 15.67; F = 20.45, p < 0.001, η² = 0.45).ConclusionChildren with ASD showed significantly lower QoL, particularly in social and school functioning, highlighting the need for targeted interventions addressing core symptoms and environmental and family factors to improve outcomes.